Efektivitas Media Wordwall dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI dan Budi Pekerti - Rahman, Muhammad Fadhillah; Rusdi, Rusdi; Al-Anshori, Habib Anwar (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract This study aims to examine the effectiveness of using Wordwall media to enhance students' learning motivation in Islamic Religious Education & Character Education at SMA Negeri 1 Loa Janan. This research is motivated by the low utilization of technology-based learning media and the students' habit of playing online games during breaks, which contributes to learning boredom, as revealed by a survey showing that 60.6% of students in class X.4 felt bored. This study employs a quantitative approach using a Pre-Experimental One Group Pretest-Posttest design, involving 30 students selected using Simple Purposive Sampling. Data collection was carried out through tests, questionnaires, observations, and documentation, and analyzed through the Wilcoxon test, confirming a significant increase in learning motivation. Results showed a significant increase in learning motivation (Asymp. Sig. 0.000 < 0.05), supporting the effectiveness of Wordwall media in this context. The average increase in pretest and posttest scores was 13.00, with a total increase of 325.00. Additionally, the questionnaire results showed that learning motivation was in the effective category with an average score of 4.10, and field observations confirmed positive student responses. Thus, Wordwall media has proven to be effective in enhancing students' learning motivation in Islamic Religious Education & Character Education at SMA Negeri 1 Loa Janan. Keywords: Effectiveness, Wordwall Media, Learning Motivation, Islamic Education, Character Education Abstrak Penelitian ini mengkaji efektivitas media Wordwall dalam meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA Negeri 1 Loa Janan. Latar belakang penelitian ini adalah rendahnya pemanfaatan media pembelajaran berbasis teknologi serta kebiasaan siswa bermain game online saat istirahat yang menyebabkan kejenuhan dalam pembelajaran, sebagaimana terungkap dari survei yang menunjukkan bahwa 60,6% siswa di kelas X.4 merasa bosan. Penelitian ini menggunakan metode kuantitatif dengan desain Pre Experimental One Group Pretest-Posttest dan sampel berjumlah 30 siswa yang dipilih menggunakan teknik Simple Purposive Sampling. Pengumpulan data dilakukan melalui tes, angket, observasi, dan dokumentasi, dan dianalisis menggunakan uji Wilcoxon. Hasil penelitian menunjukkan adanya peningkatan motivasi belajar yang signifikan dengan nilai Asymp. Sig. 0,000 < 0,05, yang berarti hipotesis alternatif (Ha) diterima. Rata-rata peningkatan skor pretest dan posttest adalah 13,00 dengan total peningkatan sebesar 325,00. Selain itu, hasil angket menunjukkan motivasi belajar berada pada kategori efektif dengan skor rata-rata 4,10, dan observasi di lapangan mengonfirmasi respon positif siswa. Media Wordwall efektif meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam & Budi Pekerti di SMA Negeri 1 Loa Janan. Kata kunci: Efektivitas, Media Wordwall, Motivasi Belajar, Pendidikan Agama Islam, Budi Pekerti